Less Is Better: Single-Digit Brain Functional Connections Predict T2DM and T2DM-Induced Cognitive Impairment - Qian, Haotian; Qin, Dongxue; Qi, Shouliang; Teng, Yueyang; Li, Chen; Yao, Yudong; Wu, Jianlin (Frontiers in Neuroscience, 2021)
Type 2 diabetes mellitus (T2DM) is of higher risk of brain damage and adversely affects cognition. The underlying neural mechanism of T2DM-induced cognitive impairment (T2DM-CI) remains unclear. This study proposes to identify a small number of dysfunctional brain connections as imaging biomarkers distinguishing among T2DM-CI, T2DM with normal cognition (T2DM-NC) and healthy controls (HC). We have recruited 22 T2DM-CI patients, 31 T2DM-NC patients and 39 HCs. The structural and resting state fMRI and neuropsychological tests are carried out. Amplitude of low frequency fluctuations (ALFF) is analyzed to identify impaired brain regions implicated with T2DM and T2DM-CI. The functional network is built and all connections connected to impaired brain regions are selected. Subsequently, L1-norm regularized sparse canonical correlation analysis and sparse logistic regression are used to identify discriminative connections and Support Vector Machine is trained to realize three two-category classifications. It is found that single-digit dysfunctional connections predict T2DM and T2DM-CI. For T2DM-CI versus HC, T2DM-NC versus HC, and T2DM-CI versus T2DM-NC, the number of connections is 6, 7 and 5 and the area under curve (AUC) can reach 0.912, 0.901, and 0.861, respectively. The dysfunctional connection are mainly related to Default Model Network (DMN) and long-distance links. The strength of identified connections significantly different among groups and correlated with cognitive assessment score (p<0.05). Via ALFF analysis and further feature selection algorithms, a small number dysfunctional brain connections can be identified to predict T2DM and T2DM-CI. These connections might be the imaging biomarkers of T2DM-CI and targets of intervention.